Genetic variation in TBC1 domain family member 1 gene associates with the risk of lean NAFLD via high-density lipoprotein - Wu, Na; Zhai, Xiangyu; Yuan, Fan; Li, Jie; Li, Dong; Wang, Jianying; Zhang, Lei; Shi, Yi; Ji, Guang; He, Guang; Liu, Baocheng (Frontiers in Genetics, 2023)
Objective: Non-alcoholic fatty liver disease (NAFLD) affects almost a quarter of the world’s population. Although NAFLD often co-exists with obesity, a substantial proportion of NAFLD patients are lean which is relatively unexplored. This study aimed to examine the association between genetic variation in candidate genes, e.g., TBC1D1 and the risk of lean NAFLD in the elderly Chinese Han population. Methods: This is an extension of the research on physical examination in the Zhanjiang community center including 5387 residents, Shanghai, China, in 2017. According to the classification in adult Asian populations, participants were categorized into four groups: lean NAFLD (BMI < 23, n = 106), non-lean NAFLD (BMI ≥ 23, n = 644), lean non-NAFLD (BMI < 23, n = 216) and non-lean non-NAFLD (BMI ≥ 23, n = 253).116 NAFLD-related candidate genes, which cover 179 single nucleotide polymorphisms (SNPs) were included in the KEGG enrichment analysis. Independent samples t-test was adopted for the group comparison. The associations between genetic variations with the specific phenotype in five genetic models were analyzed with the “SNPassoc” R package and rechecked with logistic regression analysis. Mediation models were conducted to explore whether the certain phenotype can mediate the association between SNPs and the risk of lean NAFLD. Results: Compared with lean non-NAFLD individuals, lean NAFLD patients had higher BMI, low-density lipoprotein and triglyceride, and lower HDL. The AMPK signaling pathway, which includes TBC1D1 and ADIPOQ genes, was the most significant (p < 0.001). The A allele frequency of rs2279028 in TBC1D1 (p = 0.006) and G allele frequency of rs17366568 in ADIPOQ (p = 0.038) were significantly lower in lean NAFLD. The association between rs2279028 and the risk of lean NAFLD was mediated by HDL (p = 0.014). No significant mediation effect was found between rs17366568 and the risk of lean NAFLD. Conclusion: This study, for the first time, indicated that rs2279028 of TBC1D1 may contribute to the progression of lean NAFLD through HDL. This finding provides more evidence for exploring the mechanism of lean NAFLD and suggests practical solutions for the treatment of lean NAFLD.